Holy Bible : containing Old and New Testaments : translated out of the original tongues : and with the former translations diligently compared and revised, by His Majesty's special command ...: containing Old and New Testaments : translated out of the original tongues : and with the former translations diligently compared and revised, by His Majesty's special command ... (2010) - Unknown
No abstract available